Livestock disease challenges and gaps in delivery of animal health services - Njehu, A.; Omore, Amos O.; Baltenweck, Isabelle; Muriithi, B. (International Livestock Research Institute, 2011)
The East Africa Dairy Development (EADD) project is a regional industry development program implemented by a consortium of partners led by Heifer International. It is currently being piloted in 18 sites in Kenya, 8 in Rwanda and 27 in Uganda. The overall goal of the project is to transform the lives of 179,000 families, or about 1 million people, by doubling household dairy income in 10 years through integrated interventions in dairy production, market access and knowledge application. This brief highlights key results of a baseline survey that was carried out with the objective of assessing the gaps in delivery of animal health services in Kenya, Rwanda and Uganda. Specifically, the survey assessed the main animal health problems; preventive and curative measures used to control animal diseases; livestock farmers’ access to veterinary and livestock extension services; and the cost of veterinary and livestock extension services. Details are available in the baseline survey report No. 4